Exploring the Influence of Lateral Conductivity Contrasts on the Storm Time Behavior of the Ground Electric Field in the Eastern United States - Elena Marshalko; Mikhail Kruglyakov; Alexey Kuvshinov; Benjamin S. Murphy; Lutz Rastätter; Chigomezyo Ngwira; Antti Pulkkinen (Space Weather)
Abstract The intensification of the fluctuating geomagnetic field during space weather events leads to generation of a strong electric field in the conducting earth, which drives geomagnetically induced currents (GICs) in grounded technological systems. GICs can severely affect the functioning of such infrastructure. The ability to realistically model the ground electric field (GEF) is important for understanding the space weather impact on technological systems. We present the results of three‐dimensional (3‐D) modeling of the GEF for the eastern United States during a geomagnetic storm of March 2015. The external source responsible for the storm is constructed using a 3‐D magnetohydrodynamic (MHD) simulation of near‐Earth space. We explore effects from conductivity contrasts for various conductivity models of the region, including a 3‐D model obtained from inversion of EarthScope magnetotelluric data. As expected, the GEF in the region is subject to a strong coastal effect. Remarkably, effects from landmass conductivity inhomogeneities are comparable to the coastal effect. These inhomogeneities significantly affect the integrated GEF. This result is of special importance since the computation of GICs relies on integrals of the GEF (voltages), but not on the GEF itself. Finally, we compare the GEF induced by a laterally varying (MHD) source with that calculated using the plane wave approximation and show that the difference is perceptible even in the regions that are commonly considered to be negligibly affected by lateral nonuniformity of the source. Overall, the difference increases toward the north of the model where effects from laterally variable high‐latitude external currents become substantial.